Role of NPR1 and KYP in long-lasting induced resistance by β-aminobutyric acid - Luna, Estrella; López, Ana; Kooiman, Jaap; Ton, Jurriaan (Frontiers in Plant Science, 2014)
Priming of defence increases the responsiveness of the plant immune system and can provide broad-spectrum protection against disease. Recent evidence suggests that priming of defence can be inherited epigenetically to following generations. However, the mechanisms of long-lasting defence priming within one generation remains poorly understood. Here, we have investigated the mechanistic basis of long-lasting induced resistance after treatment with ß-amino butyric acid (BABA), an agent that mimics biologically induced resistance phenomena. BABA-induced resistance is based on priming of salicylic acid (SA)-dependent and SA–independent defences. BABA-induced resistance could be detected up to 28 days after treatment of wild-type Arabidopsis. This long-lasting component of the induced resistance response requires the regulatory protein NPR1 and is associated with priming of SA-inducible genes. In contrast, NPR1-independent resistance by BABA was transient and had disappeared by 14 days after treatment. Chromatin immunoprecipitation (ChIP) assays revealed no increased acetylation of histone H3K9 at promoters regions of priming-responsive genes, indicating that this post-translational histone modification is not critical for long-term transcriptional priming. Interestingly, the kyp-6 mutant, which is affected in methyltransferase activity of H3K9, was blocked in long-lasting BABA-induced resistance, indicating a critical requirement of this post-translational histone modification in long-lasting BABA-IR. Considering that KYP suppresses gene transcription through methylation of H3K9 and CpHpG DNA methylation, we propose that KYP enables long-term defence gene priming by silencing suppressor genes of SA/NPR1-dependent genes.